2009
DOI: 10.1515/crelle.2009.068
|View full text |Cite
|
Sign up to set email alerts
|

Domains of convergence for monomial expansions of holomorphic functions in infinitely many variables

Abstract: Each bounded holomorphic function on the infinite dimensional polydisk D ∞

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 44 publications
3
48
0
Order By: Relevance
“…The proof of the last inequality follows exactly the same steps as in Section 3, using (12). To prove the first equality, let us choose r > T 1 (v) and show that r ≥ 1/BH 1 (v) .…”
Section: A Defant and P Sevilla-perismentioning
confidence: 93%
See 1 more Smart Citation
“…The proof of the last inequality follows exactly the same steps as in Section 3, using (12). To prove the first equality, let us choose r > T 1 (v) and show that r ≥ 1/BH 1 (v) .…”
Section: A Defant and P Sevilla-perismentioning
confidence: 93%
“…It is not in general true that (6) converges pointwise to P . A deep and complete study of when this happens in the scalar-valued case can be found in [12].…”
Section: Preliminariesmentioning
confidence: 99%
“…4-it is mainly based on a fundamental result from local Banach space theory due to Maurey and Pisier [15] (see the preliminaries) combined with ideas from [4,5,8].…”
Section: Corollary 1 For All Finite Dimensional Banach Spaces Y We Hamentioning
confidence: 99%
“…Very recently a thorough study on domains of convergence of monomial expansions of holomorphic functions has been made in [13]; it contains the following result that will be a key ingredient to us.…”
Section: Introductionmentioning
confidence: 99%